2020
DOI: 10.1016/j.psj.2019.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid bioactive compounds of hawthorn extract can promote growth, regulate electrocardiogram waves, and improve cardiac parameters of pulmonary hypertensive chickens

Abstract: The effect of orally administered hawthorn flavonoid extract ( HFE ) on growth, electrocardiographic waves, and cardiac parameters of pulmonary hypertensive chickens reared at high altitude (2,100 m above sea level) was examined. A total of 225 one-day-old, mixed broiler chicks (3 treatments with 5 replicates and 15 chicks per each, totally 75 birds/treatment) were assigned to 3 experimental groups: 0, 0.1, and 0.2 ml of HFE per 1 L of drinking water. Birds were administered the drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Baicalin and chrysin may reduce collagen deposition [ 68 , 153 ]. Resveratrol, curcumin, hydroxysafflor yellow A, allicin, hawthorn, and other natural products have protective effects on the heart [ 99 , 157 , 158 , 159 , 160 ]. Of course, there are other pathways, such as metabolism, genetics, etc., but they have not been summarized because fewer natural products are involved [ 65 , 164 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baicalin and chrysin may reduce collagen deposition [ 68 , 153 ]. Resveratrol, curcumin, hydroxysafflor yellow A, allicin, hawthorn, and other natural products have protective effects on the heart [ 99 , 157 , 158 , 159 , 160 ]. Of course, there are other pathways, such as metabolism, genetics, etc., but they have not been summarized because fewer natural products are involved [ 65 , 164 ].…”
Section: Discussionmentioning
confidence: 99%
“…MLB improves right ventricular remodeling in pulmonary hypertension by inhibiting the NOX/VPO1 pathway [ 44 ]. In addition, many other natural products, such as hydroxysafflor yellow A, allicin, hawthorn, and breviscapine, have a protective effect on the right ventricle through several pathways [ 158 , 159 , 160 , 161 ].…”
Section: Mechanism Of Natural Products For the Treatment Of Phmentioning
confidence: 99%
“…has been used in China for hundreds of years and is widely recognized for its therapeutic effects on anorexia and diarrhea (Kong et al, 2009; Shin et al, 2006). Recent studies have shown that the addition of hawthorn extract to broilers (Ahmadipour et al, 2020; Dai et al, 2021; Zhang et al, 2009) or juvenile golden pompano ( Trachinotus ovatus ) (Tan et al, 2017) diets significantly improved growth performance and enhanced immunity and antioxidant capacity. Yam extract can improve the growth performance and immunity of weaned rats (Kong et al, 2009) and improve the immunity of the common carp by regulating intestinal microbiota and enhancing intestinal defense barrier (Meng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The rich polyphenolic components of hawthorn peel and pulp could differentially modulate dyslipidemia, inflammation, oxidative stress, and alleviate liver injury in mice, which is the main reason for its excellent antioxidant and free radical scavenging abilities ( Han et al, 2016 ; Zhao et al, 2017 ). The mediated cardiogenic, vasodilatory and antioxidant effects of flavonoid bioactive compounds in hawthorn extracts making them beneficial in the prevention of pulmonary hypertension syndrome and heart disease ( Ahmadipour et al, 2020 ). Flavonoids and oligomeric proanthocyanidins play a major role in the protection and treatment of various CDVs ( Rigelsky and Sweet, 2002 ).…”
Section: Introductionmentioning
confidence: 99%